A cluster randomized controlled trial of the Promoting Alternative Thinking Strategies (PATHS) curriculum. (October 2016) - Humphrey, Neil; Barlow, Alexandra; Wigelsworth, Michael; Lendrum, Ann; Pert, Kirsty; Joyce, Craig; Stephens, Emma; Wo, Lawrence; Squires, Garry; Woods, Kevin; Calam, Rachel; Turner, Alex
Abstract: This randomized controlled trial (RCT) evaluated the efficacy of the Promoting Alternative Thinking Strategies curriculum (PATHS;Kusche & Greenberg, 1994 ) as a means to improve children's social–emotional competence (assessed via the Social Skills Improvement System (SSIS); Gresham & Elliot, 2008) and mental health outcomes (assessed via the Strengths and Difficulties Questionnaire (SDQ); Goodman, 1997). Forty-five schools in Greater Manchester, England, were randomly assigned to treatment and control groups. Allocation was balanced by proportions of children eligible for free school meals and speaking English as an additional language via minimization. Children ( N = 4516) aged 7–9 years at baseline in the participating schools were the target cohort. During the two-year trial period, teachers of this cohort in schools allocated to the intervention group delivered the PATHS curriculum, while their counterparts in the control group continued their usual provision. Teachers in PATHS schools received initial training and on-going support and assistance from trained coaches. Hierarchical linear modeling of outcome data was undertaken to identify both primary (e.g., for all children) and secondary (e.g., for children classified as "at-risk") intervention effects. A primary effect of the PATHS curriculum was found, demonstrating increases in teacher ratings of changes in children's social–emotional competence. Additionally, secondary effects of PATHS were identified, showing reductions in teacher ratings of emotional symptoms and increases in pro-social behavior and child ratings of engagement among children identified as at-risk at baseline. However, our analyses also identified primary effects favoring the usual provision group, showing reductions in teacher ratings of peer problems and emotional symptoms, and secondary effects demonstrating reductions in teacher ratings of conduct problems and child ratings of co-operation among at-risk children. Effect sizes were small in all cases. These mixed findings suggest that social and emotional learning interventions such as PATHS may not be as efficacious when implemented outside their country of origin and evaluated in independent trials.